ONE-YEAR RESULTS OF BRACING FOR PATELLO-FEMORAL OSTEOARTHRITIS. PROSPECTIVE RANDOMIZED STUDY - MERINO, MATHEUS GARCIA LOPES (Acta Ortop Bras, 2021)
OBJECTIVE: To compare the long-term effects of a brace designed to stabilize the patellofemoral (PF) joint in comparison to a standard neoprene sleeve for the knee with patellar hole in patients with patellofemoral osteoarthritis (PFOA). METHODS: 38 patients with PFOA and comorbidities received either a functional PF brace (Study Group, SG) or a neoprene sleeve for the knee (Control Group, CG). Both groups received clinical treatment to OA and comorbidities according to a program from the institution. Patients were evaluated with Western Ontario and MacMaster (WOMAC) and Lequesne questionnaires, 30-second chair stand test (30CST), Timed Up and Go (TUG), anthropometric measures and self-reported physical activity in minutes/week at inclusion, one, three and twelve months after placing the brace. X-Rays were taken to measure the angles. RESULTS: At one year there was more abandonment in the CG without differences in weight and body mass index between groups during the study. The SG maintained improvements in Lequesne and WOMAC total and subsets during the year, whereas the CG returned to baseline values for pain, function and total (p < 0.01). TUG and 30CST results were always better in the study group without any clinically important improvement in both groups. CONCLUSION: Long-term use of functional brace added to self-management program improves pain and function in patients with PFOA. Level of Evidence II, Lesser quality RCT (eg, < 80% followup, no blinding, or improper randomization).